INFLUENCE OF PRE-SOWING HE-NE AND SEMICONDUCTOR LASER STIMULATION ON SAINFOIN SEEDS GERMINATION FOUR AND EIGHT MONTHS POST-HARVEST - Dragoslav Djokić; Milesa Srećković; Zoran Fidanovski; Jelena Ilić; Rade Stanisavljević; Dragan Terzić; Jordan Marković; Saša Barać (Journal of Animal and Plant Sciences, 2017)
Sainfoin seeds were irradiated by four different lasers (He-Ne laser, three semiconductor lasers of wavelengths 670 nm, 890 nm and of wavelength range 630-680 nm). Each group of seed was irradiated only once, using different exposure times: 1-, 2-, 3- and 4- minutes. The same procedure was applied before autumn (four months post-harvest) and spring sowing (eight months post-harvest). Laser bio-stimulation showed that the optimal operation of the laser was at 890 nm using 3-minutes exposure time in both sowing periods. Slightly weaker, but also significant (p ≥0.01) impact on improving germination was in case of laser of 890 nm using 2- and 4- minutes of exposure time, and 630-680 nm laser using 4- minutes exposure time in both sowing periods. In the spring sowing, only laser of 632.8 nm using 3- minutes exposure time and laser of 670 nm laser between 2- and 4- minutes exposure time had significant improvement of seed germination. In the autumn sowing, He-Ne lasers (632.8 nm) using 4- minutes exposure time, semiconductor lasers of 670 nm laser using 3- minutes exposure time, and 630-680 nm laser using 3- minutes exposure time, also significantly (p ≥0.01) increased seed germination compared to control.
Keywords: post-harvest period; sainfoin; seeds; laser stimulation; germination